2007
DOI: 10.1159/000106582
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Lichen Nitidus with Involvement of the Palms following Interferon α Treatment

Abstract: Lichen nitidus is an uncommon dermatosis of unknown etiology. Here we present the case of a generalized lichen nitidus with involvement of the palms in a patient with hepatitis C after systemic treatment with interferon α and ribavirin. Furthermore in our patient we could show a strong lesional expression of MxA, a protein specifically induced by type I interferon. It is tempting to speculate that interferon α may be involved in the pathogenesis of lichen nitidus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…This drug may also induce a large number of cutaneous reactions. These are psoriasis, eczema or lichenoid eruptions, skin dryness, granulomatous infiltrates, photosensitivity and acrosyndromes [24,[25][26][27][28].…”
Section: Treatment-related Cutaneous Manifestationsmentioning
confidence: 99%
“…This drug may also induce a large number of cutaneous reactions. These are psoriasis, eczema or lichenoid eruptions, skin dryness, granulomatous infiltrates, photosensitivity and acrosyndromes [24,[25][26][27][28].…”
Section: Treatment-related Cutaneous Manifestationsmentioning
confidence: 99%
“…Berger and Dhar17 reported that LN lesions developed as a lichenoid photoeruption in advanced human immunodeficiency virus-infected patients. Moreover, a case of generalized LN in a patient with hepatitis C after systemic treatment with interferon α and ribavirin has been reported16. A relation between immunological alterations and the development of LN has also been suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Another etiologic theory of LN proposes that an active infectious agent or idiopathic response to nonviable microbial antigens (viruses, mycobacterial and treponemal species, streptococci) may activate a cell-mediated response, initiate lymphocyte accumulation, and form inflammatory papules1,16. Berger and Dhar17 reported that LN lesions developed as a lichenoid photoeruption in advanced human immunodeficiency virus-infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lichen nitidus is a rare, chronic, lichenoid inflammatory disease of unknown etiology with some overlap to lichen planus (LP) that occurs at middle age with a higher incidence in black subjects, but it is also not unusual in children. 2 LN typically affects the penis, neck, flexural surfaces of the arms, and less often the trunk. Lesions can be generalized, grouped, fleshcolored, hemorrhagic, perforating, keratodermic, and display a Koebner phenomenon.…”
mentioning
confidence: 99%
“…Flares of LN almost like LP have been reported after hepatitis vaccination, interferon (IFN)-a treatment, and in association with sarcoidosis and Crohn's disease suggestive for a common type I IFN-driven reaction. 2,4 Because IFN-a therapy is recommended for the treatment of MC in immunodeficient patients, 5 one may speculate that IFN are produced during the naturally induced immune response against MC. In the present case, MC might have spread easily on the dry atopic skin, thus inducing an IFN response which may have provoked LN.…”
mentioning
confidence: 99%